Herr Lubitsch goes to Hollywood : German and American film after World War I - Thompson, Kristin, 1950- (Film culture in transition., 2005)
The first study by an acclaimed American scholar of the artistic interdependencies between the German and the Hollywood cinema in the 1920s.